2015
DOI: 10.1021/acs.jpcc.5b06634
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Hydrogen Bonding in Indole Carboxylic Acid Clusters

Abstract: Monolayers of indole-2-carboxylic acid and indole-3-carboxylic acid on gold are studied using ultrahigh-vacuum scanning tunneling microscopy. Both molecules form symmetric, cyclic, hydrogen-bonded pentamers, a structure that is stabilized by the presence of a weak hydrogen-bond donor (NH or CH) adjacent to the carboxylic acid on the five-membered ring. In addition to pentamers, indole-2-carboxylic acid forms hexamers and catemer chains, while indole-3-carboxylic acid monolayers are generally disordered. Densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Instead, we propose the explanation that tetramers initially form in solution, either in the rapidly evaporating droplet in transit or a rapidly evaporating film at the Au(111) surface. Given past studies that have observed both direct [ 30 ] and indirect [ 13 14 19 ] evidence of the formation of metastable clusters in solution during pulse deposition, we think that this mechanism is a plausible one for the formation of these tetramers.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Instead, we propose the explanation that tetramers initially form in solution, either in the rapidly evaporating droplet in transit or a rapidly evaporating film at the Au(111) surface. Given past studies that have observed both direct [ 30 ] and indirect [ 13 14 19 ] evidence of the formation of metastable clusters in solution during pulse deposition, we think that this mechanism is a plausible one for the formation of these tetramers.…”
Section: Resultsmentioning
confidence: 77%
“…Pulse deposition usually results in a heterogeneous surface, most likely due to the fact that any cluster formation that occurs in the rapidly evaporating droplet will proceed under non-equilibrium conditions and thus can produce kinetic intermediates [ 13 14 19 , 27 30 ]. For 9,10-phenanthrenequinone we observe three broad categories of assembly: disordered molecules, rectangular tetramers, and ordered linear rows, as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution deposition has been known to result in metastable configurations, as compared to vapor-deposited monolayers of the same molecule. 18,19 In addition, because there is less thermal energy available at 78 K than at room temperature, adsorbate molecules have less energy to re-organize into a lower energy configuration, and the resulting trimer structure may be a metastable configuration that at higher temperature, could reorganize into a different configuration, in this case, tetramers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, it was shown that if the hydrogen atom is attached to a polarized carbon atom, it can form hydrogen bonds as strong as those formed by regular hydrogen-donating atoms [3,4]. Today it is generally accepted that C-H/O interactions represent true hydrogen bonds [5][6][7] and that they play significant role in the stability of nucleic acid and protein structures, enzymatic activity and crystal packing [8][9][10][11]. C-H/O interactions are essential for stabilization of protein structures since it was shown that they make up to 25% of all hydrogen bonds in the structure of proteins [12,13].…”
Section: Introductionmentioning
confidence: 99%